Audio-visual navigation reduces treatment time in deep-inspiration breath hold radiotherapy - Doležel, Martin; Odrážka, Karel; Vaňásek, Jaroslav; Hartmann, Igor; Kohlová, Tereza; Vlachová, Zuzana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
AIMS: The purpose of this study was to compare the treatment times for deep-inspiration breath hold with and without audio-visual (A-V) navigation. METHODS: We measured the real treatment time in 60 patients with breast cancer undergoing postoperative radiotherapy. Thirty consecutive patients were treated without deep-inspiration breath hold (DIBH) and another 30 patients using deep-inspiration breath hold (10 patients with DIBH only, 10 patients with DIBH using visual feedback and 10 patients with DIBH using visual feedback following breath training). The treatment time was relativized to number of fields and 100 monitor units (MU). The independent t-test was used to analyse differences between cohorts. RESULTS: The mean treatment time for patients without DIBH was 46.5 seconds per field and 90.9 seconds per 100 MU, for DIBH only 92.3 and 170.2 seconds, for DIBH with audio-visual navigation 68.1 and 133.8 seconds, and for DIBH with A-V feedback including breath training 66.1 and 132.5 seconds. The treatment times for patients treated using DIBH with visual navigation were significantly shorter in comparison with patients without visual feedback. We were not able to prove any significant benefit for breath training in terms of reducing the treatment time. CONCLUSION: Audio-visual navigation enables to significantly reduce the treatment time in comparison with DIBH without A-V feedback.
Keywords: Humans; Radiotherapy Planning, Computer-Assisted; lidé středního věku; Female; Aged; dospělí; senioři; lidé; časové faktory; Adult; Breast Neoplasms; ženské pohlaví; zadržování dechu; Middle Aged; plánování radioterapie pomocí počítače; Aged, 80 and over; nádory prsu; Breath Holding; senioři nad 80 let; Time Factors